Laseracupuntura com frequência de Nogier e seus efeitos na qualidade de vida, critérios de diagnóstico, intensidade da dor e variabilidade da frequência cardíaca em mulheres com fibromialgia: Ensaio clínico randomizado piloto - Silva, Karol Priscila Da (2021)
Introduction: Fibromyalgia is characterized by a complex rheumatologic condition with uncertain pathophysiology. Functional incapacity is the main factor that negatively impacts the quality of life of patients. Patients present with autonomic nervous system disorders such as sympathetic hyperactivity and abnormal vagal balance. In Brazil, it is present in 2.5% of the country's general population, with a prevalence in female patients. Its form of diagnosis is the diagnostic criteria created by the CAR. Treatment is aimed at clinical manifestations, through pharmacological and non-pharmacological measures, with the objective of improving symptoms. Laser acupuncture is a non-invasive technique that can be offered as a treatment to patients who are afraid of the needle. Paul Nogier, a French acupuncturist developed the use of low-intensity laser therapy in acupuncture and described laser frequencies that proved effective for stimulating acupuncture points. Objective: to analyze the effects of laser acupuncture with Nogier frequency on quality of life, on fibromyalgia diagnostic criteria, on pain intensity and on HRV in women with fibromyalgia. Methodology: Pilot Randomized Controlled Clinical Trial. Twenty women were selected, randomly divided into two groups: the IG who received laser acupuncture treatment and the CG who received an informative lecture on daily care and management of the pathology. Assessments were performed before and after the last intervention. The instruments used for evaluation were diagnostic criteria for fibromyalgia (IDG and ESS), the QIF, pain intensity (EAN) and analysis of the R-R and HRV intervals, in the domain of time and frequency. Results: When comparing the groups, a significant reduction in the variables QIF (p=0.02), IDG (p=0.03) and ESS (p=0.02) can be observed. For the EAN variables, a significant difference was observed in the GI (p=0.03), however, no significant difference was observed between the groups for EAN and HRV. Conclusion: Laser acupuncture with Nogier frequency caused a reduction in the impact of fibromyalgia on the quality of life of the patients evaluated, as well as a reduction in pain intensity. However, it did not show alterations in the autonomic pattern of the patients.